High Blood Presure : At your Fingertips - Hart, Dr. Julian Tudor (Sydney The McGraw-Hill Companies, Inc., 2003)
A practical, useful guide on the everyday issues of living with high blood pressure, that uses an easy-to-understand question-and-answer format.
Include Appendix and Index
The comprehensive and medically accurate manual on how to manage you high blood pressure.
Keywords: Hypertension -- Blood circulation disorders